The Impact of Merger and Acquisition on Firm Performance - Jiang, Yusi (2016)
M&A generally refers to mergers and acquisitions. Merger means two or more independent companies merging into a business entity, usually a dominant company absorbing one or more companies. Acquisition refers to an enterprise using cash or marketable securities to buy another company’s stock or assets, to obtain the ownership of all the assets or an asset of the enterprise or control the company. Under the background of deepening economic globalization, in order to improve the competitiveness of the industry and monopoly power, increasing the market share and industry voice and control, mergers and acquisitions of listed companies activities have become more and more actively, expanding the company size and industry competitiveness to cope with the increasingly fierce global competition. The research object of this dissertation is to investigate the impact of merger and acquisition on firm performance, using financial index method to compare the improvements of companies’ performance that have M&A activities and those have no M&A activities. At the first stage, M&A performance evaluating model is set by using finance indicators . Finance indicators method refers to use the main indicators of the financial statements to establish the comprehensive models of evaluating companies performance. This paper is divided into several parts: Chapter 1: Introduction: In this chapter, the author has presented the relevant background information, the nature and significance of the research, problems in the research, and motivation behind the research. Subsequently, the aims and questions of the research have been illustrated. Then the approaches and methodology was introduced. Finally, the paper structure has been outlined. Chapter 2: Literature Review In this chapter, the previous researches about Merger and Acquisition are deeply reviewed, this help the author to form the research basis to make further analysis. Due to the results of literature review, the model of research in this dissertation can be formed. This helps the research to be unique. Chapter 3: Methodology In this chapter, the application of the relevant methodology and method in this research were evaluated. The details of data collection include subject, instruments, administration of procedures, and research ethics were also be presented. Methodology is very important, it dominate the research process and help the author get correct results in the process of research. Chapter 4: Empirical Analysis In this chapter, empirical analysis are presented. This is a very important part of this dissertation, as all the research results are shown in this part. In this dissertation, the author used STATA 11.0 to do all the description analysis and regression analysis. This help the author quickly achieve the aim to see the results of analysis and make deep analysis about the resulst. Some results are in accordance with our predictioni, while others are not, this means that reseaons behind the abnormal results shoud be found. This is the most valuable part for a research. Chapter 5: Discussions and Conclusions The data from findings was interpreted. And some conclusions were made in a more general context. Furthermore, the limitations and further research were presented.